Microbiota Signals Suppress B Lymphopoiesis With Aging in Mice - Krambs, Joseph R.; Monlish, Darlene A.; Gao, Feng; Schuettpelz, Laura G.; Link, Daniel C. (Frontiers in Immunology, 2021)
Aging is associated with significant changes in hematopoiesis that include a shift from lymphopoiesis to myelopoiesis and an expansion of phenotypic hematopoietic stem cells (HSCs) with impaired self-renewal capacity and myeloid-skewed lineage differentiation. Signals from commensal flora support basal myelopoiesis in young mice; however, their contribution to hematopoietic aging is largely unknown. Here, we characterize hematopoiesis in young and middle-aged mice housed under specific pathogen free (SPF) and germ-free (GF) conditions. The marked shift from lymphopoiesis to myelopoiesis that develops during aging of SPF mice is mostly abrogated in GF mice. Compared with aged SPF mice, there is a marked expansion of B lymphopoiesis in aged GF mice, which is evident at the earliest stages of B cell development. The expansion of phenotypic and functional HSCs that occurs with aging is similar in SPF and GF mice. However, HSCs from young GF mice have increased lymphoid lineage output, and the aging-associated expansion of myeloid-biased HSCs is significantly attenuated in GF mice. Consistent with these data, RNA expression profiling of phenotypic HSCs from aged GF mice show enrichment for non-myeloid biased HSCs. Surprisingly, the RNA expression profiling data also suggest that inflammatory signaling is increased in aged GF HSCs compared with aged SPF HSCs. Collectively, these data suggest that microbiota-related signals suppress B lymphopoiesis at multiple stages of development and contribute to the expansion of myeloid-biased HSCs that occurs with aging.